Analyzing the Potential of E-Broking vis-Ã -vis Preferences of the Investors in Choosing a Brokerage Firm-A Study in Hyderabad - Prageetha Raju, G. (Indian Journal of Finance, 2009)
The equity broking industry in India has several unique features. It is more than a century old, dynamic and forward looking, well conversant, highly innovative and adaptable. While regulation and reforms have made major improvements in the quality of the equity markets in India, its rapid growth and development are largely due to strong and efficient market intermediation. The robustness of the Indian markets today is attributable to a healthy blend of the quality of market structure and efficient intermediation. Even as several countries are instituting procedures to commence equity derivative markets, India ranks amongst the top five countries globally in this segment, in less than five years of its introduction. This is an example of the proactive and progressive nature of the Indian brokerage industry. In the last decade, the Indian brokerage industry has undergone a dramatic transformation. From being made of close groups, the broking industry today is one of the most transparent and compliance oriented businesses. Long settlement cycles and large scale bad deliveries are a thing of the past with the advent of T+2 settlement cycle and dematerialization. Large and fixed commissions have been replaced by wafer thin margins, with competition driving down the brokerage fee, in some cases, to a few basis points.There have also been major changes in the way business is conducted. The scope of services have enhanced from being equity products to a wide range of financial services. Investor protection has assumed significance, and so has providing them with education and awareness. Greater need for capitalization has induced several firms to access the capital market; foreign firms are showing increasing interest in taking equity stakes in domestic broking firms.